Avaliação de métodos para alívio da dor na inserção do sistema intrauterino liberador de levonorgestrel em adolescentes e pacientes jovens: estudo randomizado - Elaine Cristina Fontes de Oliveira (2019)
The levonorgestrel-releasing intrauterine system (LNG-IUS) is a safe and effective method of non-permanent contraception that can be used by women, including adolescents, nulliparous or multiparous women. The reduction of the pain during insertion of the device could lead to increased use of the device. The purpose of this study was to evaluate the use of the levonorgestrel-releasing intrauterine system in young patients with the aim of answering the following question: what is the best method for patient relief during the insertion of LNG-IUS in young patients: intracervical anesthesia with lidocaine or naproxen? The study evaluated the use of LNG-IUS in 100 healthy, nulligest or multiparous women aged 15-24 years. Patients were randomized to receive 550 mg naproxen 30 minutes prior to IUS insertion or 6 ml of 2% lidocaine without a vasoconstritor intracervical anesthesia. Forty-nine patients received oral naproxen and 51 received intracervical anesthesia. The visual analogue scale (VAS) was used to quantify the pain. The patients were followed up for a period of 12 months. Demographic and gynecological variables were similar in the 2 groups. The results show that there was a statistically significant difference (p <0.001) between the 2 methods of pain relief, and the pain scale of the patients treated by the naproxen method (mean = 7.3) was significantly higher than in the patients treated by the intracervical anesthesia method (Mean = 5.4). The only complication observed during insertion was the vasovagal reflex (7%). The insertion was performed without difficulty in 82% of the patients. The maintenance rate of the method was 89.1% in the first year of use, with high satisfaction rates (93.9%) with its use. Fifty percent of the women entered amenorrhea in the first year. The insertion of the LNG-IUS was considered easy and successful in the majority of the young patients, with high rates of continuation and satisfaction in the first year of its use. Performing cervical blockade with 2% lidocaine in the four quadrants of the cervix reduced the pain intensity during insertion of the device in young patients compared to those using oral naproxen